ADAPTATION AND TRANSFORMATION OF MEXICAN VERNACULAR ELEMENTS IN ART MUSIC: A CASE STUDY OF MANUEL PONCE’S SONATA FOR VIOLIN AND PIANO - Maria-Magdalena SUCIU; Botond SZŐCS; Stela DRĂGULIN (Studia Universitatis Babeş-Bolyai. Musica, 2025)
The adaptation of folk traditions into composed art music has played a crucial role in shaping national musical identities. This article explores the ways in which Mexican vernacular elements are integrated, transformed, and recontextualized within composed works, with a particular focus on the Sonata for Violin and Piano by Manuel M. Ponce. By examining the broader processes of adaptation, the authors aim to highlight how composers navigate the balance between preservation and innovation, using folk material as a foundation for new artistic expressions. The analysis addresses melodic, rhythmic, and harmonic transformation techniques, situating Ponce’s approach within a broader historical and cultural framework.